2020
DOI: 10.1016/j.jhepr.2020.100119
|View full text |Cite
|
Sign up to set email alerts
|

Adding the oxygen carrier M101 to a cold-storage solution could be an alternative to HOPE for liver graft preservation

Abstract: Background & Aims: Hypothermic oxygenated machine perfusion (HOPE) is a promising technique for providing oxygen to the liver during graft preservation; however, because of associated logistical constraints, addition of an oxygen transporter to static cold-storage solutions (SCS) might be easier. M101 is marine worm haemoglobin that has been shown to improve kidney preservation in the clinic when added to SCS. This study evaluated the effects of the addition of M101 to SCS on the quality of pig liver graft pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 27 publications
0
33
0
1
Order By: Relevance
“…The initial transplantation-related research was performed by Thuillier et al They demonstrated that Hemarina M101 has a beneficial effect during SCS before kidney transplantation by decreasing chronic fibrosis and organ dysfunction [ 82 ]. Alix et al compared SCS solution with Hemarina M101 versus SCS solution alone during porcine liver graft preservation, showing higher ATP levels in the SCS with Hemarina M101 group after 80 min [ 42 , 83 ]. M101 was also used in preclinical trials as an additive to the perfusion solution during HMP in a marginal kidney porcine model.…”
Section: Overview Of Oxygen Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial transplantation-related research was performed by Thuillier et al They demonstrated that Hemarina M101 has a beneficial effect during SCS before kidney transplantation by decreasing chronic fibrosis and organ dysfunction [ 82 ]. Alix et al compared SCS solution with Hemarina M101 versus SCS solution alone during porcine liver graft preservation, showing higher ATP levels in the SCS with Hemarina M101 group after 80 min [ 42 , 83 ]. M101 was also used in preclinical trials as an additive to the perfusion solution during HMP in a marginal kidney porcine model.…”
Section: Overview Of Oxygen Carriersmentioning
confidence: 99%
“…The [42,83]. M101 was also used in preclinical trials as an additive to the perfusion solution during HMP in a marginal kidney porcine model.…”
Section: Natural Extracellular Oxygen Carrier Hemarina M101mentioning
confidence: 99%
“…With interest we have read the recent article by Alix et al describing the effect of M101 (a marine worm hemoglobin) added to the static cold storage (SCS) solution for liver preservation. 1 In this study, the authors compared preservation of porcine liver grafts with SCS supplemented with M101 to SCS alone, or with hypothermic oxygenated machine perfusion (HOPE), followed by transplantation. The authors claim that adding the oxygen carrier M101 to SCS could be an alternative to HOPE for liver graft preservation.…”
mentioning
confidence: 99%
“…In this issue, Alix et al compared the addition of an oxygen carrier (M101) to SCS with SCS alone and the HOPE device in a pig model of liver transplantation. 13 They observed that SCS + M101 and HOPE were better than SCS alone in different preservation parameters (oxidative stress, inflammatory mediators). After 1 hour of preservation, HOPE seemed to be better than SCS + M101.…”
Section: Coagulation In Cirrhosis Is a Complex Issue Where The Classical Tests (International Normalized Ratio [Inr] Activated Partial Thmentioning
confidence: 99%